THE INFLUENCE OF INQUIRY METHOD IN MOTIVATING THE SMP' STUDENTS - Agi Ginanjar (Universitas Negeri Yogyakarta, 2015)
This study was aimed at comparing the result of the students’ learning motivation by usinginquiry method and direct method and ﬁ nding out the interaction between the learning method andthe goal of learning towards students’ learning motivation. This study used experimental methodwith the factorial design 2 x 2 (ANAVA).The population was consisted of 272 students of 8th gradeof SMP 1 Ngamprah. It was involved 8 classes; each class consisted of 35 students. This study usedpurposive sampling technique with two-way ANAVA. The results shows that the inquiry learningmethod is much better than direct learning method with 31,591 value and there is no correlationbetween learning methods and students' scores.